NLRX1 Inhibits LPS-Induced Microglial Death via Inducing p62-Dependent HO-1 Expression, Inhibiting MLKL and Activating PARP-1 - Yu-Ling Huang; Duen-Yi Huang; Vladlen Klochkov; Chi-Ming Chan; Yuan-Shen Chen; Wan-Wan Lin (MDPI AG, 2024)
The activation of microglia and the production of cytokines are key factors contributing to progressive neurodegeneration. Despite the well-recognized neuronal programmed cell death regulated by microglial activation, the death of microglia themselves is less investigated. Nucleotide-binding oligomerization domain, leucine-rich repeat-containing X1 (NLRX1) functions as a scaffolding protein and is involved in various central nervous system diseases. In this study, we used the SM826 microglial cells to understand the role of NLRX1 in lipopolysaccharide (LPS)-induced cell death. We found LPS-induced cell death is blocked by necrostatin-1 and zVAD. Meanwhile, LPS can activate poly (ADP-ribose) polymerase-1 (PARP-1) to reduce DNA damage and induce heme oxygenase (HO)-1 expression to counteract cell death. NLRX1 silencing and PARP-1 inhibition by olaparib enhance LPS-induced SM826 microglial cell death in an additive manner. Less PARylation and higher DNA damage are observed in NLRX1-silencing cells. Moreover, LPS-induced HO-1 gene and protein expression through the p62-Keap1-Nrf2 axis are attenuated by NLRX1 silencing. In addition, the Nrf2-mediated positive feedback regulation of p62 is accordingly reduced by NLRX1 silencing. Of note, NLRX1 silencing does not affect LPS-induced cellular reactive oxygen species (ROS) production but increases mixed lineage kinase domain-like pseudokinase (MLKL) activation and cell necroptosis. In addition, NLRX1 silencing blocks bafilomycin A1-induced PARP-1 activation. Taken together, for the first time, we demonstrate the role of NLRX1 in protecting microglia from LPS-induced cell death. The underlying protective mechanisms of NLRX1 include upregulating LPS-induced HO-1 expression via Nrf2-dependent p62 expression and downstream Keap1-Nrf2 axis, mediating PARP-1 activation for DNA repair via ROS- and autophagy-independent pathway, and reducing MLKL activation.